FIELD EVALUATION OF NEWCASTLE DISEASE VACCINE OF VG\GA IN STRAIN SEVERAL COMMERCIAL BROILER FARMS IN JAVA - Charles Rangga Tabbu (Jurnal Sain Veteriner, 1996)
This field evaluation was conducted to study the level of protection, post vaccinal reactions and zootechninal performance of groups of chickens which have been vaccinated with Newcastle disease (ND) vaccine of VG/GA strain.This evaluation was done in 26.000 broilers from 4 farms, which have different condition in management practices and were located in different areas of Java.Chickens were vaccinated with VGAGA vaccine or with B-l/La Sota vaccine with/without inactivated ND. Serological tests were done at the age of 28 and 35 days, whereas challenge test with local ND virus isolates was done at the age of 45 days. Results of field evaluation indicated that in broilers, the VG/GA vaccine induced a high level of protection agamst the challenge test with a local (Indonesia) ND virus isolate and against infection with field ND virus. Statistical analysis indicated that the hemagglutination inhibition (HI) titers against NDV were significantly higher (P < 0,05) in group of chickens vaccinated with VG/GA with/without inactivated ND compared to group of chickens vaccinated with B-l/La Sota with/without inactivated ND vaccine. In certain conditions, the post vaccinal reactions were milder and the zootechnkal performance was better in groups of chickens vaccinated with VG/GA strain compared to groups vaccinated with B-l/La Sota.